Liturgy’s outlook on the oikumene exposes distorted attitudes and memories of ecumenism - Ferdinand P. Kruger; Barend J. de Klerk (Verbum et Ecclesia, 2023)
This article explored the interplay between ecumenism and people’s distorted attitudes. Viewed from a South African historical perspective, faith communities have endured a robust experience of denominationalism. The authors were thus interested in the influential impact of attitudes and people’s memories in a praxis that recognises the importance of ecumenism but demonstrates limited efforts to promote it. This aspect is evident in the descriptive-empirical section of this research. Ironically, people are firm in their confession, which explicitly embraces ecumenicity. However, distorted attitudes present challenges in the praxis thereof. The authors applied visualisation as part of the research methodology, and executed the research as developing from the description to systemising (exploring practical wisdom and understanding) to strategising (practising strategic, practical theology). The notion of the oikumene pinpoints the kingdom’s interest, but people are focused on liturgical and other differences, which challenges ecumenical relationships. The authors presented the following research questions: How can an elucidation of ecumenical liturgy serve as a means to uncover negative attitudes and bad memories while simultaneously providing building blocks for fostering the realisation of the oikumene? We offer systemising perspectives to denote the importance of crossing borders to promote ecumenical relations and debate the power of liturgy to enhance awareness.